Non-pharmacological self-management for people living with migraine or tension-type headache: a systematic review including analysis of intervention components. Issue 8 (11th August 2017) - Probyn, Katrin; Bowers, Hannah; Mistry, Dipesh; Caldwell, Fiona; Underwood, Martin; Patel, Shilpa; Sandhu, Harbinder Kaur; Matharu, Manjit; Pincus, Tamar
Abstract : Objectives: To assess the effect of non-pharmacological self-management interventions against usual care, and to explore diﬀerent components and delivery methods within those interventions Participants: People living with migraine and/or tension-type headache Interventions: Non-pharmacological educational or psychological self-management interventions; excluding biofeedback and physical therapy. We assessed the overall effectiveness against usual care on headache frequency, pain intensity, mood, headache-related disability, quality of life and medication consumption in meta-analysis. We also provide preliminary evidence on the effectiveness of intervention components and delivery methods. Results: We found a small overall effect for the superiority of self-management interventions over usual care, with a standardised mean diﬀerence (SMD) of −0.36 (−0.45 to −0.26) for pain intensity; −0.32 (−0.42 to −0.22) for headache-related disability, 0.32 (0.20 to 0.45) for quality of life and a moderate effect on mood (SMD=0.53 (−0.66 to −0.40)). We did not find an effect on headache frequency (SMD=−0.07 (−0.22 to 0.08)). Assessment of components and characteristics suggests a larger effect on pain intensity in interventions that included explicit educational components (−0.51 (−0.68 to −0.34) vs −0.28 (−0.40 to −0.16)); mindfulness components (−0.50 (−0.82 to −0.18) vs 0.34 (−0.44 to −0.24)) and in interventions delivered in groups vs one-to-one delivery (0.56 (−0.72 to −0.40) vs −0.39 (−0.52 to −0.27)) and larger effects on mood in interventions including a cognitive–behavioural therapy (CBT) component with an SMD of −0.72 (−0.93 to −0.51) compared with those without CBT −0.41 (−0.58 to −0.24). Conclusion: Overall we found that self-management interventions for migraine and tension-type headache are more effective than usual care in reducing pain intensity, mood and headache-related disability, but have no effect on headache frequency. Preliminary findings also suggest that including CBT, mindfulness and educational components in interventions, and delivery in groups may increase effectiveness. Trial registration number: PROSPERO 2016:CRD42016041291